Investigation of microfiltration performance of denitrifying granular sludge developed in sequencing batch reactors - Liu, Yajuan (2012)
Nitrogen-containing compounds released into the environment can create serious problems, such as water eutrophication, deterioration of water quality and potential hazard to human health. Biological nitrogen removal through two-stage nitrification and denitrification has thus been practiced for decades. Bulking sludge in denitrification has often been reported. In order to overcome such problem, denitrifying membrane bioreactor (MBR) has drawn more and more attention. However, biofouling due to microbial attachment onto membrane surfaces remains a big challenge that in turn hinders further application of denitrifying MBR technology. The aims of this thesis were to look into denitrifying granular sludge MBR for effective control of biofouling, and further investigate the biofouling mechanism. For these purposes, the study was carried out in two parts: (i) development of denitrifying granular sludge at different cycle times of 4, 6 and 8 h and feed calcium concentrations of 0, 50 and 100 mg Ca2+/L, and (ii) investigation of fouling mechanisms of denitrifying granular sludge. It was found that a short cycle time could favor denitrifying granulation and helped improve the granules properties, such as size, settleability, strength and bioactivity, whereas a high calcium concentration could facilitate the formation of big size and dense denitrifying granules.